2021
DOI: 10.5194/egusphere-egu21-13821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Projections of regional climate change in Ukraine based on multi-model ensembles of Euro-CORDEX

Abstract: <p>Climate change is one of the major challenges for future development in every country including Ukraine where actual warming already has impacted many sectors, population, and ecosystems. Recently, the International Initiative of Coordinated Downscaling Experiment for Europe (Euro-CORDEX) has provided RCM data for 0.1<sup>o</sup> grid. This detailed RCM projection dataset is an excellent basis for estimation of exposure and vulnerability to climate change of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to their results, it was that the consequences of the warming may be more signifi cant than had previously been believed (Palmer, 2021). According to current climatic scenarios of moderate (RCP4.5) and high (RCP8.5) concentrations of greenhouse gases, it is expected that up to 2050, the average air temperature in Ukraine's territory will increase by 1.2-3.0 degrees respectively (Krakovska et al, 2021). The prediction demonstrates the probability of a decrease in the amount of summer precipitation or its preservation at the current level, which may enhance droughts and their negative effect on agriculture (Wilson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, it was that the consequences of the warming may be more signifi cant than had previously been believed (Palmer, 2021). According to current climatic scenarios of moderate (RCP4.5) and high (RCP8.5) concentrations of greenhouse gases, it is expected that up to 2050, the average air temperature in Ukraine's territory will increase by 1.2-3.0 degrees respectively (Krakovska et al, 2021). The prediction demonstrates the probability of a decrease in the amount of summer precipitation or its preservation at the current level, which may enhance droughts and their negative effect on agriculture (Wilson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SU is likely to increase in the near future in Croatia as well, especially in the coastal locations (by ~10 days; Brankovic et al ., 2012). RCM simulations show an increase in the number of SU and a decrease in the case of FD in Ukraine (Krakovska et al ., 2021), in Kolasin, Montenegro (Buric and Doderovic, 2020) and in Cluj Napoca, Romania (Ciupertea et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The future climate of Ukraine has already been studied using different datasets (Krakovska et al, 2018(Krakovska et al, , 2021Snizhko, Shevchenko, Buznytskyi, et al, 2020;Snizhko, Shevchenko, Didovets, et al, 2020). In particular, it was found that the temperature would increase by ~3.0°C, and precipitation would slightly decrease in Southern Ukraine, where Odesa is located, by the mid of the current century.…”
Section: Introductionmentioning
confidence: 99%